Laparoscopy for evaluating mesenteric lymphangiomatosis: A case report - Yin, Yefeng; Wang, Rongdi; Wang, Xishan (Frontiers in Oncology, 2022)
BACKGROUND Lymphangiomatosis is an extremely rare disease that can involve soft tissue, bone and spleen and can be characterized by lymphangioma. Only a few cases of colon and mesenteric lymphangiomatosis have been reported. We report a case presenting with fatigue, periumbilical pain, and intermittent bloody stools. This patient underwent a series of examinations. Exploratory laparoscopy, in particular, revealed very valuable images and videos of this disease, which can provide evidence for the diagnosis of this disease. CASE SUMMARY In this case, the patient had fatigue, periumbilical pain, and intermittent bloody stools. Colonoscopy indicated numerous variable-sized hyaline cysts in colon. Submucosal puncture was performed during colonoscopy. The patient was admitted to the hospital again due to periumbilical pain. B-ultrasound and abdominal CT scan showed multiple hypoechoic nodules in the mesenteric area. exploratory laparoscopy was performed, and histopathology revealed that D2-40 was positive. On the basis of auxiliary examination and laparoscopic biopsy, surgeons and pathologists gave the diagnosis of mesenteric lymphangiomatosis. CONCLUSION Clinicians need to improve their comprehensive knowledge of NKTCL, and combination of clinical symptoms, histological characteristics, as well as colonoscopy biopsies should be considered to improve the diagnosis and thereby reduce misdiagnosis.